DEVELOPMENT OF MULTIMODAL E-MODULE FOR CREATIVE WRITING BASED ON SOUTH SUMATRAN LOCAL WISDOM - Nuzula, Khalidatun; Turama, Akhmad Rizqi; Putri, Astrid Yulinda; Sholikhah, Hani Atus; Monita, Ananda Nadya (TELL - US JOURNAL, 2026)
This research aims to develop a multimodal e-module for creative writing based on South Sumatran local wisdom to enhance writing skills and strengthen the cultural identity of students in the Indonesian Language and Literature Education Study Program at FKIP Universitas Sriwijaya. The research method employed Research and Development (R&D) using an adapted ADDIE model up to the Development stage (Analysis, Design, Development). Research subjects included 94 students for needs analysis, 3 expert validators (media, culture, language), and 30 students for practicality testing. The Analysis phase identified gaps in creative writing comprehension (62.77%) and South Sumatran local wisdom knowledge (34.04%). The Design phase produced a structured e-module blueprint with seven learning modules (biography, autobiography, short story, poetry, drama script, folktale, feature) integrating South Sumatran cultural elements such as songket weaving, gending sriwijaya dance, pempek cuisine, Musi River, limas traditional house, and Palembang folktales. The Development phase created an e-module using Canva and FlipHTML5 platforms, featuring a South Sumatran local wisdom inspiration bank, video tutorials, sample works, writing guides, and learning evaluations. Expert validation results showed the e-module was highly valid with an average of 89.65% (media expert 91.50%, cultural expert 87.57%, language expert 86.25%). Practicality test results indicated the e-module was highly practical with an average of 88.29%, with the local wisdom aspect receiving the highest score (90.83%). This research produced an e-module product that integrates creative writing and South Sumatran local wisdom with a multimodal approach for prospective Indonesian language teachers. These findings imply that integrating regional cultural content into digital learning media can simultaneously strengthen students’ creative writing competencies and cultural literacy. The e-module serves as a replicable model for incorporating local wisdom into higher education curricula across Indonesia, with broader implications for culturally responsive pedagogy in teacher education programs.